2009
DOI: 10.1039/b900165d
|View full text |Cite
|
Sign up to set email alerts
|

A novel europium(iii) complex with versatility in excitation ranging from infrared to ultraviolet

Abstract: One- and two-photon absorption properties of a novel europium(III) complex containing a hemicyanine cation are investigated in this paper; in which the sensitization wavelength of europium(III), induced by beta-diketonate ligands, is in the ultraviolet range, and the hemicyanine(aminostyrylpyridinium) cation extends the sensitization wavelength of Eu(III) to visible region. Furthermore, under 1.06 microm ultrashort pulse laser excitation, the complex exhibits effective europium(III) luminescence induced by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…[4][5][6][7] Europium(III) complexes with b-diketonate ligands have attracted considerable attention because of their chemical stability, ease of preparation and noticeable emission properties due to the high energy transfer rate from ligands to central Eu 3+ ions (known as the antenna effect). [8][9][10] It was reported that LEDs using europium(III)-b-diketonate complexes as red phosphors could emit highly monochromatic red light with half peak bandwidths of only 5-10 nm resulting from the 5 D 0 -7 F 2 electronic transitions. 6,7,11 However, high-energy oscillators in ligands, such as C-H and O-H bonds (typically found in b-diketonate ligands), can quench the excited states nonradiatively and shorten the excited-state lifetimes because their energy levels of multiphonon oscillation-coupling are just close to the 5 D 0 state of the Eu 3+ ion.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Europium(III) complexes with b-diketonate ligands have attracted considerable attention because of their chemical stability, ease of preparation and noticeable emission properties due to the high energy transfer rate from ligands to central Eu 3+ ions (known as the antenna effect). [8][9][10] It was reported that LEDs using europium(III)-b-diketonate complexes as red phosphors could emit highly monochromatic red light with half peak bandwidths of only 5-10 nm resulting from the 5 D 0 -7 F 2 electronic transitions. 6,7,11 However, high-energy oscillators in ligands, such as C-H and O-H bonds (typically found in b-diketonate ligands), can quench the excited states nonradiatively and shorten the excited-state lifetimes because their energy levels of multiphonon oscillation-coupling are just close to the 5 D 0 state of the Eu 3+ ion.…”
Section: Introductionmentioning
confidence: 99%
“…1) cation that extends the sensitization wavelength into the visible. 25 Recently Maury et al sensitized an ytterbium complex using an elegant macrocyclic ligand based on the triaza-cyclononane platform (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The superior luminescent properties of europium complexes are characterized by the narrow-line emission of Eu 3 + in the red-light region, with acceptable transparence for many biosamples, large Stokes shifts, and long luminescence lifetimes. [3][4][5] Remarkable progresses have been achieved in the design and synthesis of Eu 3 + complexes with excellent two-photon excitation (TPE) luminescence properties, 4,[6][7][8][9][10][11][12][13][14][15][16][17] and several ones have been successfully applied in the multi-photon-excitation bio-imaging of cells. 8,9,18 In comparison with free Eu 3 + complex molecules, bionanoprobes prepared by encapsulating proper Eu 3 + complexes into water-dispersible and biocompatible nanoparticles possess the additional benefits of markedly enhanced luminescent brightness, chemical stability and photostability, as well as lower cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%